100 years of the modern German tax system: Foundation, reforms, and challenges - Stefan Bach (DIW Weekly Report, 2019)
The tax and fiscal reforms headed by German finance minister Matthias Erzberger in 1919 and 1920 fundamentally reshaped German public finances. The total tax revenue as a percentage of GDP, or tax-to-GDP ratio, doubled and increased continually until the end of World War II. Since the 1950s, the tax-to-GDP ratio has remained between 22 and 24 percent of GDP most of the time. West Germany's economic recovery and the Wirtschaftswunder (economic miracle) following World War II began with the implementation of high income and corporate tax rates and wealth taxes, which were later decreased gradually. During this time, the welfare state was expanded and social security contributions increased markedly. Beginning in the mid-1970s, weak growth and fiscal consolidation dominated tax and fiscal policies. In the 1980s, tax policies were characterized by supply-side economics, and since the 1990s, by a (neo-)liberal reform agenda. Recently, the issue of distribution has come back into focus. Due to new challenges such as globalization, digitalization, social changes, immigration, maintaining infrastructure, and climate change, a substantial decrease in the tax burden is not expected.
Keywords: N44; H20; H11; 330; history of taxation; tax system; tax reform